Nurses' professional competences in providing care to the injured in earthquake: A qualitative study - Soheila Ahangarzadeh Rezaei; Alireza Abdi; Farzaneh Akbari; Khalil Moradi (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: Iran has experienced an increasing number of earthquake disasters in the past three decades. Due to nurses' unique role as professional and volunteer responders in times of disaster, more information is required regarding the capabilities they need to provide more effective care during the crisis. The aim of this study was to identify professional capabilities needed by nurses to provide care to the injured of earthquake. MATERIALS AND METHODS: The present study was conducted as a qualitative conventional content analysis, and data collection was carried out through 16 semi-structured and in-depth interviews with the nurses involved in providing care to the injured in the Kermanshah earthquake. The data were analyzed following Graneheim and Lundman's approach. RESULTS: Data analysis led to the emergence of 427 primary codes, 10 subcategories, and four categories. The four categories included clinical competence (professional knowledge and clinical skills), personal competences (communication skills, resiliency, and creativity and innovation in providing care), ethical competence (commitment to ethics and professional responsibility), and essential skills in caring for the injured (skills in triage, psychological care skills, and skills in observation and monitoring) CONCLUSION: The present study identified a wide range of professional capabilities required by nurses in disasters. Given that nurses do not acquire some of these specialized and technical skills during their education, it is recommended to enhance the professional capacity of nurses in disasters. In addition, special training programs in this field can be incorporated into the curriculum of nursing programs and in-service nursing education.